POLITENESS STRATEGIES IN RESPONDING TO COMPLIMENTS IN JAVANESE - Sukarno, Sukarno (Indonesian Journal of Applied Linguistics, 2015)
Abstract:Â  Javanese has been studied from many different perspectives. However, no one discusses how Javanese respond to compliments politely. The aim of this study is to investigate the politeness strategies as applied to respond to compliments by the Javanese people in Jember, East Java. The notion of politeness plays crucial role in the realization of speech acts (utterances and verbal communication) in Javanese, such as responding to compliements. As utterances and verbal communications should be interpreted based on the sosio-cultural background, the politeness strategies in responding to compliments in Javanese cannot be separated from the concepts of the Javanese culture, such as: andhap-asor (lowering oneself, while exalting the others) and tanggap ing sasmita (understanding the hidden meaning). First, as a Javanese, one must be able to apply the concept of andhap-asor in responding to compliments by denigrating himself. Second, a good Javanese should also have a sense of tanggap ing sasmita while responding to compliments. Consequently, failure to apply one of the cultural factors can be detrimental to the speaker, reducing the harmony of the conversation. This paper examines how politeness is manifested and conveyed within the major framework of the Javanese culture. This study is about socio-cultural pragmatics in which utterances are discussed in relation to their situations, and the cultural background which support them. The data are in the form of dialogues among students-teachers, and students-students which show the different social status among the interlocutors. The data of this research were collected by recording, and by note taking (for the parts in which recording is not possible). The data are aimed to generate the strategies used by the Javanese (in Jember, Indonesia) to build politeness strategies in responding to compliments. Finally, the data of this research are examined both from the general theory of politeness, and the Javanese cultural concepts (andhap-asor and tanggap ing sasmita). This study provides important findings which reveal that responding to compliments in Javanese can be achieved in five strategies: (1) disagreeing and denigrating, (2) disagreing and raising a question, (3) accepting and turning back, (4) accepting and giving explanation, and (5) accepting only, or accepting and offering.Â